ANALISIS KINERJA KEUANGAN UNTUK MENGUKUR TINGKAT KESEHATAN KEUANGAN KOPERASI (CASE STUDY OF KUD BALAM SEJAHTERA PT. SALIM IVOMAS PRATAMA, BAGAN SINEMBAH) - Andre Kurniawan; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to determine the Financial Soundness of the Balam Sejahtera Cooperative KUD for the 2016-2020 period seen from seven aspects, namely aspects of capital, quality of productive assets, management, efficiency, liquidity, independence and growth, and the identity of the cooperative. The approach used is a descriptive approach. The type of data used is secondary data. Data collection techniques were obtained through interviews and financial statement documents such as: balance sheet, report on remaining operating results (SHU), and report on calculation of operating results (PHU). In relation to the health of cooperatives, a health assessment model of the savings and loan business is used which refers to the Ministerial Regulation no. 14/Per/M.KUKM/XII/2009. The results of this study indicate that the health level of the Balam Sejahtera KUD for the calculation of seven aspects for each year, starting from 2016 the total score obtained was 54.75 with the unhealthy category, in 2017 and 2018 it increased to get a total score of 62.30 and 60, 55 with a fairly healthy category. Followed by 2019 and 2020 the total score decreased and got a score of 52.80 and 52.55 in the less healthy category. Thus it can be said that the health level of cooperatives for the 2016-2020 period is less healthy, the average score of the Balam Sejahtera KUD for the 2016-2020 period is 56.59 in the unhealthy category. Keywords: health level, seven aspects, score.